Pengembangan “INDOLATURE”: Aplikasi Website Bertemakan Kebudayaan Sastra Indonesia - Dion Darmawan; Wishnu Wijaya; Christian Surjanto; Ngakan Made Prakasa Judha; Muhammad Dana Paramita (Bina Nusantara University, 2022)
Indonesian literature is a field of science that studies poetry, prose, stories, novels, scripts, rhymes, and other literary works. Along with the development of the era and technology, interest in reading and interest in making Indonesian literature is decreasing. Along with the development of communication and information technology, the dissemination of information becomes faster and wider, for example through the use of the internet. Based on the results data from the research, the authors developed a website-based application that can publish Indonesian literary works with an attractive and interactive display for makers and readers in order to preserve and increase public interest in Indonesian literary culture. The research method used for data collection is using observation techniques, questionnaires, and interviews. As for the development of this website-based application using the Agile Development approach, with the Kanban method. The programming language used is JavaScript using the React.js and Express.js libraries and frameworks, as well as MongoDB for data storage. The results of this research, it is hoped that with the rapid advancement of science and technology, we want to combine technology and Indonesian literature by creating a web application that can help connect readers with other literary writers and reintroduce Indonesian literary culture more. We hope that this application can increase public interest in Indonesian literary culture. In addition, it is hoped that the wider community can access Indonesian literary works more quickly, easily, and comfortably.